The equation of the quadratic function in standard form as required in the task content is; f(x) = -x² + 12x - 43.
<h3>Standard form equation of a quadratic function.</h3>
It follows from the task content that the standard form equation of the quadratic function is to.be determined.
Since the standard form equation can be derived from the vertex form equation as follows;
f(x) = a (x - h)² + k
f(x) = a (x - 6)² - 7
Hence, to find the value of a, Substitute x = 8 and f(x) = -11 so that we have;
-11 = a (8 - 6)² - 7
-11 = 4a - 7
4a = -4
a = -1.
Hence, the equation in vertex form is; f(x) = -1 (x -6)² - 7 and when expressed in standard form we have;
f(x) = -1(x² - 12x + 36) - 7
f(x) = -x² + 12x - 43
Therefore, the required equation in standard form is; f(x) = -x² + 12x - 43.
Read more on quadratic functions;
brainly.com/question/25841119
#SPJ1
Answer: Organisms go through mitosis that allows new identical cells to be made.
explanation:
mitosis also occures when cells are worn out or are injured and the mitosis will replace the injured cells
It's a number that can be expressed as a fraction, the numerator and the denominator of which, are integers.
Answer:
I think it is 7.6
the square root of 58 is 7.6
7.6 x2 = y y/2= 7.6 again
Use linear combination to solve this. It is much faster than substitution. I would start by multiplying the bottom equation by -1.
<span>4x-7y=3
-x+7y=15</span>
Then, add the two equations together. The result is:
3x=18.
You've eliminated one variable. Now you can solve for the other one.
Divide both sides by 3 to get
x=6
Plug this into one of the original equations, then solve for y
-(6)+7y=15
7y=21
y=3
Check your work by plugging these values into both equations to see if they remain true